Desmoplastic ameloblastoma of mandible - Nair, Preeti P (BMJ Publishing Group, 2013)
Desmoplastic ameloblastoma is one of the six histopathological subtypes of ameloblastoma. The age and gender groups affected by desmoplastic are similar to those affected by the conventional ameloblastoma. It usually presents as a painless enlargement of the jaw. Owing to its deceptive radiological appearance as a mixed radiopaque–radiolucent lesion, it is often mistaken as a fibro-osseous lesion. Histologically, desmoplastic ameloblastoma has a densely collagenised and hypocellular stroma, where the epithelium tends to proliferate in the form of cords and nests instead of cellular islands. Most desmoplastic ameloblastomas display occasional classic islands of follicular ameloblastoma among the predominant strands and cords. Studies have shown that desmoplastic ameloblastoma shows a tendency to recur. We present a rare case of a tumour occurring in the anterior mandibular region in a 60-year-old man over a period of 11/2 months.